An analysis of trends in Irish public healthcare expenditure and staffing - Richard Whyte; Maev-Ann Wren; Conor Keegan; Aoife Brick (The Economic and Social Research Institute (ESRI), 2020)
This report analyses changes in public current and capital healthcare expenditure (HCE) (2004 to 2017), and its components, along with trends in HSE staffing and pay expenditure (2007 to 2017). This report adopts an inclusive approach to the measurement of HCE and HCE is defined in gross terms which includes any income receipts used to fund public care. Healthcare expenditure trends are adjusted to account for population growth and ageing, and price effects, over the period of analysis. Nominal public current HCE increased by 74.2 per cent between 2004 and 2017, equating to a 4.4 per cent annual average increase. However, with adjustment for demographic and price effects, public current HCE increased by a more modest 0.2 per cent on an annual average basis. Furthermore, the introduction of the Employment Control Framework (in 2009) reduced HSE staffing levels and pay expenditure but was associated with substantial increases in agency pay and HSE superannuation expenditure. Overall, discussion and assessment of HCE would benefit from placing trends into the context of changing prices and demographics. The long-term effects of measures, such as incentivised early retirement schemes, aimed at short-term cost-saving need to be considered as they may, in fact, lead to increased expenditure over time. Insights from this analysis of historic Irish healthcare expenditure trends may prove useful to policymakers' approach to ongoing financing of the Irish healthcare system in the COVID-19 healthcare crisis.
Keywords: 330; Gesundheitswesen; Coronavirus; Gesundheitsversorgung; Irland